RENEWAL OF FATTY ACIDS IN THE MEMBRANES OF VISUAL CELL OUTER SEGMENTS - Bibb, Carol (The Rockefeller University Press, 1974)
The renewal of fatty acids in the visual cells and pigment epithelium of the frog retina was studied by autoradiographic analysis of animals injected with tritiated palmitic, stearic, or arachidonic acids. Most of the radioactive material could be extracted from the retina with chloroform-methanol, indicating that the fatty acids had been esterified in lipids. Analysis of the extracts, after injection of [(3)H]palmitic acid, revealed that the radioactivity was predominantly in phospholipid. Palmitic acid was initially concentrated in the pigment epithelium, particularly in oil droplets which are storage sites for vitamin A esterified with fatty acid. The cytoplasm, but not the nucleus of these cells, was also heavily labeled. Radioactive fatty acid was bound immediately to the visual cell outer segment membranes, including detached rod membranes which had been phagocytized by the pigment epithelium. This is believed to be due to fatty acid exchange in phospholipid molecules already situated in the membranes. Gradually, the concentration of radioactive material in the visual cell outer segment membranes increased, apparently as a result of the addition of new phospholipid molecules, possibly augmented by the transfer from the pigment epithelium of esterified vitamin A. Injected fatty acid became particularly concentrated in new membranes which are continually assembled at the base of rod outer segments. This localized concentration was short-lived, apparently due to the rapid renewal of fatty acid. The results support the conclusion that rods renew the lipids of their outer segments by membrane replacement, whereas both rods and cones renew the membrane lipids by molecular replacement, including fatty acid exchange and replacement of phospholipid molecules in existing membranes.